New species of Pycnogonum (Pycnogonida: Pycnogonidae) from Green Island, Taiwan, with an additional note on the holotype of P. spatium - Lee, Damin; Kim, Won (Zootaxa, 2020)
We report the discovery of a new species of the genus Pycnogonum Brünnich, 1764 found in the shallow waters of Green Island, Taiwan. Pycnogonum (Nulloviger) granulatum sp. nov. is characterized by the presence of the granular integument, a dorsal tubercle on the proboscis, the transverse ridges on the dorsal surface of the trunk, and the spines on the ventral surface of the tibia, tarsus, and propodus having cleft tips. Because the male gonopores are present and ovigers are absent, the present species belongs to the subgenus Nulloviger. The present species has been compared with P. (N.) moolenbeeki Stock, 1992, P. (N.) lobipes Stock, 1991, P. (N.) tuberculatum Clark, 1963, P. nodulosum Döhrn, 1881, and P. spatium Takahashi, Dick & Mawatari, 2007. Among the congeners, P. spatium is geographically the closest congener, of which type locality is Amami Island, Japan. The holotype of P. spatium was loaned from Hokkaido University Museum (ICHUM) and re–examined. To determine the exact gender of the holotype of P. spatium, additional investigations of the coxal pellicula and gonopores are required.